Combination of Ratio Derivative Spectrophotometry with Simultaneous Standard Additions Method for Determination of Sulfamethoxazole and Trimethoprim - Hajian, R.; Haghighi, R.; Shams, n. (Asian Journal of Chemistry, 2010)
Ratio derivative spectrophotometrie method has been developed for the simultaneous determination of sulfamethoxazole (SMX) and trimethoprim (TMP) at micromolar levels in Britton Robinson buffer (pH 9) medium. In this method, the overlapping spectra of sulfamethoxazole and trimethoprim were well resolved by making use of the first derivative of the ratios of their direct absorption spectra. The derivative ratio absorbances of sulfamethoxazole and trimethoprim were measured at 256 and 293 nm, respectively for their quantification. The method is simple, fast and does not require separation of sulfamethoxazole and trimethoprim. Another salient feature of the method is that simultaneous standard additions of both analytes permitted to resolve matrix effect and quantification at a unique standard addition plot. Sulfamethoxazole and trimethoprim were determined in the concentration range of 5-150 μmol L-1 (SMX/TMP ratio varying from about 1 to 5) in the same aliquot with a good precision and accuracy. The recommended procedure was successfully applied for analysis of sulfamethoxazole and trimethoprim in combination dosage forms.